Kajian Persepsi Pengunjung Terhadap Potensi dan Kelayakan Taman Hutan Raya Gunung Kunci Sumedang sebagai Lokasi Forest Healing: An Assessment of Visitors’ Perceptions Regarding the Potential and Feasibility of Taman Hutan Raya Gunung Kunci Sumedang as a Forest Healing Destination - Wahyuni, Dwi; Darliana, Ina; Tiara Kusumawardhani, Dina; Wilujeng, Sri (JURNAL HUTAN TROPIKA, 2025)
This study aims to assess visitors’ perceptions of the potential and feasibility of Taman Hutan Raya (Tahura) Gunung Kunci in Sumedang Regency as a forest healing destination. The research employed a descriptive quantitative approach through a visitor perception survey focusing on facilities, services, and environmental comfort. Data were collected from three main sites amphitheater, viewing post, and bunker with 40 respondents selected using accidental sampling. The results revealed that most visitors rated the area as “Excellent” (60%) and “Good” (40%) in terms of facilities, services, and comfort. Overall, the facilities in Tahura Gunung Kunci are adequate and safe, although some areas, such as shelters and walkways around the bunker, require maintenance. The visitors’ positive perception indicates that Tahura Gunung Kunci has strong potential to be developed as a forest healing-based ecotourism destination that promotes health, education, and community well-being.